A COMPARATIVE ANALYSIS OF RETURNS, RISK, AND COEFFICIENT OF VARIATION IN ISLAMIC BANKING FINANCING IN INDONESIA - Awwalunnisa, Nur (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2016)
Abstrak This study aims to examine the differences between rates of return, risk measured by standard deviation and coefficient of variation between mudharabah-musyarakah financing and murabahah financing in Islamic banking. This study uses the financial reports of Bank Syariah Mandiri (BSM), Bank Negara Indonesia Syariah (BNI Syariah), and Bank Rakyat Indonesia Syariah (BRI Syariah) for the period 2010-2014. The analysis technique used a paired samples t-test to compare the difference between the two means of two paired samples, assuming that the data was normally distributed. To test whether the data was normally distributed or not, a normality test was conducted using the One Sample Kolmogorov Smirnov Test. Data that was not normally distributed used a non-parametric difference test using the Wilcoxon Signed-Rank Test. The results of the study show that there are no significant differences between the rates of return, risk, or coefficient of variation in mudharabah-musyarakah financing and murabahah financing. Sharia banks are expected to increase financing in both mudharabah-musyarakah and murabahah financing. Islamic banks are expected to maintain their income from murabahah financing, which is known to generate greater income compared to mudharabah-musyarakah financing. Islamic banks must also increase their income from mudharabah-musyarakah financing because Islamic banks are essentially known for their financing system that uses profit and loss sharing agreements. Keywords: Rate of return, Risk, Mudharabah-Musyarakah financing, Murabahah financing.